Association Between Systemic Therapy and/or Cytoreductive Nephrectomy and Survival in Contemporary Metastatic Non-clear Cell Renal Cell Carcinoma Patients - Luzzago, Stefano; Palumbo, Carlotta; Rosiello, Giuseppe; Knipper, Sophie; Pecoraro, Angela; Mistretta, Francesco Alessandro; Tian, Zhe; Musi, Gennaro; Montanari, Emanuele; Soulières, Denis; Shariat, Shahrokh F; Saad, Fred; et al. (European urology focus, 2021)
BACKGROUND: Optimal management of metastatic non-clear cell renal cell carcinoma (non-ccmRCC) remains largely unknown. OBJECTIVE: To test the effect of systemic therapy (ST) and/or cytoreductive nephrectomy (CNT) on overall mortality (OM) in patients with non-ccmRCC. DESIGN, SETTING, AND PARTICIPANTS: Within the Surveillance, Epidemiology and End Results (SEER) registry (2006-2015), we identified patients with papillary, chromophobe, sarcomatoid, and collecting duct metastatic renal cell carcinoma (mRCC). OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Temporal trends (estimated annual percentage change [EAPC]), Kaplan-Meier plots, and multivariable Cox regression models were used. RESULTS AND LIMITATIONS: Of 1573 patients with non-ccmRCC, 22%, 25%, 25%, and 28% underwent no treatment, ST, CNT, and CNT with ST, respectively. Between 2006 and 2015, rates of CNT and the combination of CNT and ST decreased (EAPC: -6.3% and -3.2%, respectively). Conversely, rates of no treatment and ST increased over time (EAPC: 4.6% and 7.5%, respectively). In multivariable Cox regression models, relative to no treatment, ST (hazard ratio [HR]: 0.5; p < 0.001), CNT (HR: 0.4; p < 0.001), and CNT with ST (HR: 0.3; p < 0.001) were associated with lower OM. Histological subtypes were associated with OM, relative to papillary renal cell carcinoma (RCC): chromophobe (HR: 0.7; p < 0.01), sarcomatoid (HR: 2.1; p < 0.001), and collecting duct RCC (HR: 1.9; p < 0.001). Limitations include the impossibility to stratify patients according to mRCC risk groups. CONCLUSIONS: Most non-ccmRCC patients are treated with a combination of CNT and ST or CNT alone or ST alone. The rates of ST alone are increasing. Conversely, the rates of combined CNT and ST and CNT alone are decreasing. These observed temporal patterns of treatment rates are counterintuitive with respect to associated OM benefits, where combination of CNT and ST, as well as CNT alone, resulted in the lowest absolute OM, relative to ST alone, or, even worse, no treatment. PATIENT SUMMARY: We investigated the effect of treatment modalities on survival of patients with metastatic non-clear cell renal cell carcinoma. The combination of cytoreductive nephrectomy and systemic therapy confers greater benefit with respect to single treatments alone.
Keywords: karcinom z renálních buněk; Histological subtypes; nádory ledvin; lidé; Cytoreductive nephrectomy; Overall mortality; cytoredukční chirurgie; nefrektomie; Humans; Metastases; Carcinoma, Renal Cell; Non–clear cell renal cell carcinoma; Cytoreduction Surgical Procedures; Kidney Neoplasms; Systemic therapy; Nephrectomy